Association with polymorphic marmoset cytochrome P450 2C19 of in vivo hepatic clearances of chirally separated R-omeprazole and S-warfarin using individual marmoset physiologically based pharmacokinetic models. (3rd October 2018) - Kusama, Takashi; Toda, Akiko; Shimizu, Makiko; Uehara, Shotaro; Inoue, Takashi; Uno, Yasuhiro; Utoh, Masahiro; Sasaki, Erika; Yamazaki, Hiroshi
Abstract: 1. Simulated clearances of R -warfarin and efavirenz were recently reported for individual cynomolgus monkeys genotyped for cytochrome P450 2C19 and 2C9, respectively. To expand and verify this modeling procedure, simulations of R/S -omeprazole and R/S -warfarin clearances after oral administrations in individual marmosets were performed using individual simplified physiologically based pharmacokinetic (PBPK) modeling consisting of gut, liver and central compartments. 2. Pharmacokinetics of R/S -omeprazole were chirally determined using the previously reported plasma microsamples in this study. The areas under the plasma concentration/time curves (AUC) of R -omeprazole and S -warfarin, but not S -omeprazole and R -warfarin, after oral administrations in the P450 2C19 homozygous mutant group were significantly higher than those in the wild-type group. These modeled hepatic intrinsic clearances were also significantly associated with the marmoset P450 2C19 genotypes. Other parameter values, e.g. absorption rate constants or systemic circulation volumes, were not likely determining factors. 3. The reported individual AUC values measured in 4–6 marmosets after oral R -omeprazole and S -warfarin administrations were significantly correlated with the AUC values predicted using the PBPK models after virtual administrations. 4. This study indicates that clearances of R -omeprazole, S -warfarin and related medicines associated with polymorphic P450 2C19 in individual marmosets can be simulated using simplified individual PBPK models.